AlkAniline‐Seq: Profiling of m7G and m3C RNA Modifications at Single Nucleotide Resolution. Issue 51 (16th November 2018) - Marchand, Virginie; Ayadi, Lilia; Ernst, Felix G. M.; Hertler, Jasmin; Bourguignon‐Igel, Valérie; Galvanin, Adeline; Kotter, Annika; Helm, Mark; Lafontaine, Denis L. J.; Motorin, Yuri
Abstract: RNA modifications play essential roles in gene expression regulation. Only seven out of >150 known RNA modifications are detectable transcriptome‐wide by deep sequencing. Here we describe a new principle of RNAseq library preparation, which relies on a chemistry based positive enrichment of reads in the resulting libraries, and therefore leads to unprecedented signal‐to‐noise ratios. The proposed approach eschews conventional RNA sequencing chemistry and rather exploits the generation of abasic sites and subsequent aniline cleavage. The newly generated 5′‐phosphates are used as unique entry for ligation of an adapter in library preparation. This positive selection, embodied in the AlkAniline‐Seq, enables a deep sequencing‐based technology for the simultaneous detection of 7‐methylguanosine (m 7 G) and 3‐methylcytidine (m 3 C) in RNA at single nucleotide resolution. As a proof‐of‐concept, we used AlkAniline‐Seq to comprehensively validate known m 7 G and m 3 C sites in bacterial, yeast, and human cytoplasmic and mitochondrial tRNAs and rRNAs, as well as for identifying previously unmapped positions. Abstract : Deep sequencing was applied in a new concept of library preparation for detection of RNA modifications. Modified RNA is treated by alkaline hydrolysis, dephosphorylated, and subjected to aniline cleavage of abasic sites. The resulting 5′‐phosphates in RNA are used for specific ligation of the sequencing adapter. The method can be applied for specific and sensitive detection of m 7 G, m 3 C, and (D) residues in RNAs.